PERKAWINAN MARPARIBAN DALAM MASYARAKAT BATAK TOBA DAN HALANGAN NIKAH DALAM KANON 1091 - Gregorius Risky Kombongkila (Aggiornamento, 2021)
This writing focuses on looking at the marriage of the Batak Toba society which is studied through the perspective of The Canonical Law Book of The Canon 1091. The paper methodology uses primary and secondary data collection. Primary data is obtained through interviews, while secondary data was obtained through literature review regarding the study of Toba Batak marriages and their intricacies from the perspective of the catholic church.All of data relate to the marriage norms of the catholic church and is more focused on the obstacles to marriage. Writer finds that the Mapariban marriage system in Toba society according to the canonical law book of the Catholic Church (Codex Iuris Canonici) is prohibited.